Measuring Interpersonal Visual Relationships in Healthcare Facilities: The Agent Visibility Model and SAVisualPower Tool. (October 2019) - Lim, Lisa; Kim, Minseok; Zimring, Craig M.
Visibility has a significant impact on health-related outcomes and experiences of users in healthcare settings. Built environments determine interpersonal visual relationships between users and control their ability to see (or be seen by) others. Despite this importance, metrics that fully and precisely describe these interpersonal visual relationships are lacking. In this article, we introduce the Agent Visibility Analysis Model and the SAVisualPower software, which enable person-centric visibility analysis for quantifying visual relationships both among users and between users and visual targets. The model precisely captures users' visibility by reflecting the orientation of users and by differentiating visual contents of the users—space, other users, and targets. By providing practical examples of the new model using layouts from previous studies, this article describes specific visibility metrics that can be analyzed by the new tool and how the tool can be applied to design and research in healthcare settings for improved user experiences.